JOB SECURITY AND WELL-BEING AMONG PRIVATE WORKERS IN MALAYSIA - Daud, Noraishah (Journal of Technology Management and Business, 2017)
Job security has become an interesting issue in the workplace since 25 years ago. Although the economic crisis has affected the world and the country since the 1970â€™s until now, the issue of job security has been given less attention. The issue of job security has never been scientifically conducted in Malaysia. Previous studies tend to focus on job satisfaction, organizational commitment and job performance. Some of the changes that occur in the workplace around the world forcing workers to question on their job security.Â Job security is the most important determinant of the well-being of the employees. The objectives of this study is to look at the relationship between job security and well-being of workers.Â The instrument used in this study is a set of questionnaire consistingÂ job security and well-being.This study was carried out in several banks and factories in the district of Batu Pahat and Kluang involving 600 workers which made up of 200 bank employees, electronic factory workers and textile factory workers each. Job security is measured using the Job Security Scale by Lahey & Kuhnert’s (1988) which was adopted by MacNeil (1994). Well-being Scale has been used by Mauno and Kinnunen (1999) that is designed to measure the health of the normal population. Both scales have been translated using the back translation method. Data collected were then analysed using Pearson correlation, T-test and ANOVA using SPSS.The Pearson correlation analysis showed that there is a significant relationship between job security and well-being of employees. This relationship means that when employees feel their work is guaranteed and they feel safe, this will affect the improvement of the well-being of employees. Bank employees showed a higher job security. This is probably because a career in the bank is rather more secure because there are a number of banks for example Maybank, which has many branches in Malaysia and also overseas. The findings show that employees have a high level of job security even in a desperate state.Â Such information is very useful to the management organizations to maintain job security among workers. The management also needs to find ways to enhance job security experience so it can hinder the well-being of workers in the workplace. Since it is difficult to change the objectives of the organization and the environmental factors that contribute to job insecurity, thus it is crucial to prevent the job insecurity. The findings on well-being can help individuals to find solutions towards reducing economic pressure and thus increase the level of physical health, psychological and family.Â This is important to ensure that Malaysians have always been in a high level of well-being.Â In addition, the study results can be used by the management organization to enhance the comfort of the workplace, improve health benefits and provide better workplaces.